Behandlungskonzepte zur Rekonstruktion bei ausgedehnten Unterkieferdefekten - Freier, Kolja; Mertens, Christian; Engel, Michael; Hoffmann, Jürgen (HNO, 2013)
Tumours of the mandibular bone or adjacent soft tissue often necessitate mandibular resection. Subsequent primary bone reconstruction to achieve optimal functional and aesthetic results has been made possible by microvascular surgical techniques and now represents the international gold standard. Microvascular reanastomosis of autologous bone grafts from the iliac crest or fibula is the most common procedure for reconstruction of the mandible. The localisation and extent of the expected defect, as well as a patient's overall condition and ability to tolerate long surgical procedures must be carefully considered before deciding upon the course of treatment. Additional microvascular reanastomosis of soft tissue flaps and stereolithographic models facilitate preoperative planning and broaden the surgical spectrum. Following successful reconstruction of the bone, insertion of dental implants and prosthetic rebuilding are required to complete rehabilitation, including restoration of the patient's ability to chew and speak. The authors recommend specialised oncologic centres for such complex surgical reconstructions.
Published: 29 December 2012
Gesehen am 07.05.2021